Identification and structural characterization of serobactins, a suite of lipopeptide siderophores produced by the grass endophyte Herbaspirillum seropedicae. (16th January 2013) - Rosconi, Federico; Davyt, Danilo; Martínez, Verónica; Martínez, Marcela; Abin‐Carriquiry, Juan Andrés; Zane, Hannah; Butler, Alison; de, Emanuel M.; Fabiano, Elena
Summary Herbaspirillum seropedicae Z67 is a diazotrophic endophyte able to colonize the interior of many economically relevant crops such as rice, wheat, corn and sorghum. Structures of siderophores produced by bacterial endophytes have not yet been elucidated. The aim of this work was to identify and characterize the siderophores produced by this bacterium. In a screening for mutants unable to produce siderophores we found a mutant that had a transposon insertion in a non‐ribosomal peptide synthase (NRPS) gene coding for a putative siderophore biosynthetic enzyme. The chemical structure of the siderophore was predicted using computational genomic tools. The predicted structure was confirmed by chemical analysis. We found that siderophores produced by H. seropedicae Z67 are a suite of amphiphilic lipopeptides, named serobactin A, B and C, which vary by the length of the fatty acid chain. We also demonstrated the biological activity of serobactins as nutritional iron sources for H. seropedicae. These are the first structurally described siderophores produced by endophytic bacteria.